1990
DOI: 10.1017/s0003356100005298
|View full text |Cite
|
Sign up to set email alerts
|

Diet selection in pigs: choices made by growing pigs given foods of different protein concentrations

Abstract: To test the proposition that growing pigs, when given a choice between two foods, are able to select a diet that meets their requirements, and to investigate the rules of diet selection, four foods (L, A, B and H) with similar energy yields, but different concentrations of crude protein (CP) (125, 174, 213 and 267 g CP per kg fresh food respectively) were formulated. The four foods were offeredad libitumeither singly, or as a two-way choice using all the six possible pairs, to 40 individually caged pigs from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(75 citation statements)
references
References 11 publications
2
73
0
Order By: Relevance
“…Calculations and statistical analysis Diet selection patterns were traced by plotting the cumulative difference between the intakes of WBG and SBM (CD ¼ WBG-SBM) against the cumulative feed intake (CFI ¼ WBG þ SBM), as described by Kyriazakis et al (1990). The crude preference values were calculated dividing the consumption of SBM by the total feed consumption (WBG þ SBM) as described Robertson et al (2006).…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…Calculations and statistical analysis Diet selection patterns were traced by plotting the cumulative difference between the intakes of WBG and SBM (CD ¼ WBG-SBM) against the cumulative feed intake (CFI ¼ WBG þ SBM), as described by Kyriazakis et al (1990). The crude preference values were calculated dividing the consumption of SBM by the total feed consumption (WBG þ SBM) as described Robertson et al (2006).…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…Although food selection research has shown that pigs are able to discriminate between nutritionally different foods and can select foods appropriately to meet individual nutritional requirements (Kyriazakis et al, 1990;Roth et al, 2006), there has been little research into food selection by pigs to promote a medical or pharmacological advantage, a phenomenon sometimes referred to as 'self-medication'. In our study, naïve weaned piglets did not select the advantageous food, possibly due to unpleasant organoleptic properties associated with high levels of ZnO inclusion in the food.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that, given the opportunity to recognise the benefits associated with the consumption of the ZnO supplemented food via a training period; pigs may show quite different preferences to those reported in this experiment. A training period allows pigs to experience foods individually and wait for the postingestive consequences and has been shown to be effective in other studies (Kyriazakis et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…It was assumed that the pig will attempt to consume an amount of feed that will satisfy its energy and protein requirements for potential daily gain and maintenance (Kyriazakis et al, 1990;Kyriazakis and Emmans, 1999). The same regulation does not seem to apply for P (Pomar et al, 2006;Lopes et al, 2009).…”
Section: Methodsmentioning
confidence: 99%